Ownership Structure, Corporate Governance, and Corporate Social Responsibility with Financial Performance as Intervening - Ariful Habib, Anang; Miqdad, Muhammad; Sayekti, Yosefa (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
Corporate Social Responsibility (CSR) programs are carried out by entities in the hope of getting legitimacy and positive values ​​from the community. So, companies can survive and develop, and it can increase profitability in the future. CSR has a relationship with Good Corporate Governance (GCG), Ownership Structure, and Financial Performance. This research aims to analyze the effect of the ownership structure and good corporate governance on corporate social responsibility disclosure through finance performance. The interpretation technique of the sample that is used in this research is purposive sampling. That is the manufacturing company listed on the IDX period 2017 – 2019. The data analysis method that is used is the path analysis. The resulting research is the managerial ownership influence at finance performance significantly. Institutional ownership is not influenced by finance performance. The foreign ownership influence at finance performance significantly. The measure of commissioner council influence at finance performance significantly. The Audit Committee has a positive effect on financial performance. Managerial ownership has a positive effect on CSR. Institutional ownership is no significant effect on CSR. Foreign ownership has a significant effect on CSR. The measure of Commissioners council has a significant effect on CSR. The Audit Committee has a significant effect on CSR. Financial performance has a significant effect on CSR.